BURIAL PROTOCOL DURING COVID-19 PANDEMIC; COMPARATIVE STUDY AMONG ISLAMIC LAW, STATE LAW AND OTHER COUNTIRES REGULATIONS - Hotmaria Hertawaty Sijabat (Pimpinan Cabang Muhammadiyah Kramat Jati, 2020)
Burial process during Covid-19 Pandemic has become a debate. Though nowadays, the debate has been reduced, writer felt the need to conduct research on burial process during Covid-19 Pandemic from different perspective, such as Islamic law, state law and from other countries regulations. The research is a normative legal research using secondary data and qualitative analysis. Secondary data consisted of primary legal sources in forms of regulations, secondary legal sources in forms of expert opinions, and tertiary legal sources that support the primary and secondary legal sources. Finding and analysis proved that in principle the burial process and procedure during Covid-19 Pandemic are relatively the same, that the protocol is made with one purpose to prevent further infection of Covid-19.